Effect of Diabetic Medication on Cardiovascular Risk and Microvascular Complication in Diabetic Patients: Retrospective Cohort Study - Sudhakar Pachiappan, Anju Sukumaran, Soni Rose Mathew, Stephy Deena Varghese, Tintu Aloysious (Journal of Applied Pharmaceutical Science, 2018)
This study was deliberate to evaluate the effects of diabetic medication on micro vascular and macro vascular complications in diabetic patients. In this retrospective study observational data collected from medical records of type 2 diabetic mellitus (T2DM) patients with index oral hypoglycemic medication over the period of 2009 to 2014, by using the medical record department databases of Vivekananda Medical Care Hospital, Tamil Nadu-25. They were categorised into nine groups based on the treatment received such as metformin alone, sulfonylureas alone, sulfonylureas added to metformin, metformin added to sulfonylureas, metformin with insulin added later, sulfonylureas with metformin, metformin and sulfonylureas with insulin added later, sulfonylureas and metformin with pioglitazone added later, sulfonylureas, metformin and voglibose added later. In Cox regression analyses, we estimated comparative risks for mortality due to cardiovascular problems and cardiovascular hospitalization among study cohorts, with metformin monotherapy as the reference group. The results showed that metformin monotherapy shows less cardiovascular and micro vascular events. Sulfonylurea monotherapy shows significant higher CV risk ratio. Initial sulfonylurea mono therapy with later metformin prescription and initial metformin therapy with later sulfonylureas prescription shows higher CV risk ratio as next to the sulfonylurea monotherapy and increased microvascular complication as compared to the metformin monotherapy. In conclusion the microvascular and macrovascular risks are higher in sulfonylurea alone or in combination with other agents as compared to the metformin monotherapy which has low incidence of cardiovascular risk ratio in type 2 diabetic mellitus.
Keywords: Type 2 Diabetes mellitus,microvascular risk,cardiovascular risk, oralantidiabetic drugs, Insulin.